2018
DOI: 10.1111/jcmm.13575
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism and therapy application of necrosis during myocardial injury

Abstract: Necrosis is an ancient topic which gains new attraction in the research area these years. There is no doubt that some necrosis can be regulated by genetic manipulation other than an accidental cell death resulting from physical or chemical stimuli. Recent advances in the molecular mechanism underlying the programmed necrosis show a fine regulation network which indicates new therapy targets in human diseases. Heart diseases seriously endanger our health and have high fatality rates in the patients. Cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 84 publications
(144 reference statements)
0
30
0
Order By: Relevance
“…Growing evidence from basic and clinical experiments has demonstrated that cardiomyocyte apoptosis is associated with the occurrence and development of ischemic cardiomyopathy (12,34). Apoptosis is an important cause of myocardial cell injury and cardiac function decline following MIR (12,35). The results of the present study demonstrated that MIRI increased the levels of myocardial injury markers CK and LDH, and increased the proportion of myocardial cells undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence from basic and clinical experiments has demonstrated that cardiomyocyte apoptosis is associated with the occurrence and development of ischemic cardiomyopathy (12,34). Apoptosis is an important cause of myocardial cell injury and cardiac function decline following MIR (12,35). The results of the present study demonstrated that MIRI increased the levels of myocardial injury markers CK and LDH, and increased the proportion of myocardial cells undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is the first established programmed cell death and has been studied intensively in the past 2 decades. In addition to the apoptotic cell death, other modes of programed cell death have recently been identified and are demonstrated to contribute to the pathogenesis of cardiovascular diseases (Figure 2) [45]. Understanding the roles of different cell death processes in cardiovascular diseases and the underlying signaling pathways will improve the therapeutic strategy.…”
Section: Ros and Programed Cell Deathmentioning
confidence: 99%
“…Necrosis is the death of local tissue cells characterized by changes in enzyme solubility. Primary manifestations include cell swelling, organelle disintegration and protein denaturation . Apoptosis is an active death mode of cells that plays an important role in maintaining stability of the internal environment .…”
Section: Discussionmentioning
confidence: 99%
“…Primary manifestations include cell swelling, organelle disintegration and protein denaturation. 33 Apoptosis is an active death mode of cells that plays an important role in maintaining stability of the internal environment. 34 Morphological characteristics of apoptosis include F I G U R E 5 Effect of Dex on the expression of ERS-dependent apoptotic protein after SCIRI.…”
Section: Spinal Cord Ischaemia-reperfusion Injury Can Lead To Dysfuncmentioning
confidence: 99%